Interação de fibroblastos associados ao câncer em co-cultura com linguagens tumorias mamárias e a resposta terapêutica em o uso da melatonina - Maschio, Larissa Bazela [UNESP] (2015)
Mammary tumors are the most common tumors among women and female dogs. Fibroblasts associated with cancer (CAFS) are the most abundant cells in the tumor microenvironment, able to mediate inflammatory responses acting in the differentiation and tumor progression. Melatonin is associated with mechanisms of action with oncostatics effects and oncoprotectors, and works to reduce the formation of surrounding fibroblasts in breast cancer. The objectives of this study were to assess the action of melatonin on mammary tumor cell lines human and canine metastatic (MDA-MB-231 and CF-41) and in co-culture with primary CAFS on cell viability and expression of proteins involved in the processes of angiogenesis, inflammation and apoptosis searching for the understanding of proteins interaction in the main signaling pathways active in the tumorigenic process. Cell viability was assessed by MTT assay and the semi-quantitative protein analysis by Membrane Antibody Array after treatment with melatonin. It was found that 1 mM of Melatonin reduced cell viability in both cell lines, human and canine CAFS and their co-culture (p <0.05). The semi-quantitative protein analysis after melatonin treatment showed a reduction of the expression of seven pro-angiogenic proteins and increased TIMP-1 and IL-6 protein in MDA-MB-231 cells and reduced IL-6 and MCP-1 and increased leptin, TGF-β, VEGF and thrombopoietin in the co-culture (p <0.05). Nineteen pro-inflammatory cytokine protein were reduced and I-309 increased in MDA-MB-231 cells (p <0.05). In the co-culture, six pro-inflammatory proteins were underexpressed and the IL-4, MCP-3 and SCF proteins were increased the expression (p <0.05). Twelve pro-apoptotic proteins increased and decreased expression of caspase-3 in MDA-MB-231 cells (p <0.05). In the co-culture, an increase of BIM, HPS27 and IGF-1R proteins and TNF-RII reduction was observed (p <0.05)...